Occupational Changes in Union Territory of Ladakh: A Study of Leh District - Sandup, Rigzin (Journal of Humanities and Social Sciences Studies, 2020)
This paper looks at occupational changes in Leh district over the last three decades. This includes the workforce engaged in agricultural sector and non-agriculture sector. The paper is completely based on secondary data, which is Census of India. The successive Census reports indicate a shift from the traditional sector i.e. agriculture to non-traditional sector i.e. service sector. This increase in non-traditional sector mostly consists of workforce in tourism, government servants, shopkeepers, military and para-military personnel etc.